Taking the long view on short-run marginal emissions: how much carbon does flexibility and energy storage save? - Grunewald, P; Aunedi, M; Nosratabadi, SM; Morstyn, T; Savelli, I; Kumtepeli, V; Howey, D (Oxford University Press, 2023)
Grid-scale electricity storage will play a crucial role in the transition of power systems towards zero carbon. During the transition, investments need to be channeled towards technologies and locations that enable zero carbon operation in the long term, while also delivering security of supply and value for money. We discuss metrics and market signals that are needed to guide this transition towards clean, secure and affordable solutions. Paradoxically, carbon metrics play an important role, but become less effective as a decision tool once the system approaches zero carbon. We critically assess the role of marginal and average emission and question the allocation of marginal emissions in systems where combinations of renewables and storage deliver flexibility. We conclude that, for strategic investments, short-term market signals may not always deliver sufficiently fast or far-sighted outcomes and operational decisions need to consider the merit order of demand as well as supply.